Modelling of transportation policies to encourage shifting from private car to the public transport usage in Putrajaya - Amiruddin Ismail,; Haider Farhan Hashim, (Fakulti Kejuruteraan ,UKM,Bangi., 2015)
The rapid growth of car ownership in Malaysia has led to a number of problems such as air contamination, traffi c jams, numerous accidents, extensive fuel consumption and greenhouse effect. The proper solution is by increasing awareness about it and transferring to public transport. This paper includes vast information concerning main differences between workers who use train, bus or their car to go to work to Putrajaya administration area. It also contains information about creating transportation policies meant for encouraging car owners to start using bus on a regular basis. The survey lasted for more than one month and it included 220 respondents who needed to fi ll out three parts of the questionnaires and provide main travel characteristics, personal information, and name strategies that would inspire people to start using buses on a regular basis. The prime goal of this research is to use logistic regression for creating a model that would illustrate the transfer by using few variables such as gender, age, the level of education, occupation, travel time and cost, as well as car ownership. Education level and occupation were two most important factors that would show the possibility of shifting to public transport. The percentage of respondents who preferred using their own car to go to work or run errands is rather high at 86.1% on average. After that, there is 8.9% of bus travellers and 5% of train travellers. However, 70% of car users stated that they would use a bus in case of decreased time of bus travel and increased parking charges to RM 5 per hour.